Attractiveness of the Study of Chemistry and Employment in the Chemical Industry from the Point of View of the Czech Public - Lošťáková, Hana; Jelínková, Martina; Petrík, Denis (Česká společnost průmyslové chemie, 2018)
The chemical industry, like all technical sectors, is currently suffering from a shortage of skilled labour. It is therefore very important to increase the interest in the study of chemistry and chemical technology at secondary and higher education institutions, as well as to increase the attractiveness of employment in the chemical industry. To increase its attractiveness, we need to know how young people and the general public perceive the attractiveness of chemistry and employment in the chemical industry. It is about finding out to what extent wages in this sector, labour demands, working conditions and career growth opportunities are attractive. The paper defines the general aspects of employment attractiveness and summarizes the results of primary quantitative research focused on the perception of the attractiveness of employment in the chemical industry from the point of view of the Czech public and, within it, from the point of view of secondary school students. The research was carried out in 2017 by the method of personal interviewing with the public in the East Bohemian region. The sample size was 1364 respondents selected by quota selection. It also summarizes the results of research of the same focus in a group of 391 secondary students studying in the 3rd year of schools completed with the secondary school exit exam or "maturity diploma" (GCSE). We examined the perception of the demands of chemistry and chemical technology, the demands on knowledge and skills, the prestige of work, the attractiveness of work, safety at work, remuneration, working conditions, the attractiveness of employee benefits, career growth opportunities. The research has shown that the public in the East Bohemia region considers the study of chemistry and chemical technology to be challenging and, at the same time, rather practical, rather interesting and rather prestigious. The attractiveness of employment in the chemical industry is perceived by the public in the East Bohemian region controversially. Employment in this industry is considered rather well paid, rather prestigious, interesting especially in the area of research and development, but with worse, less secure working conditions, threatening health, with higher demands on the qualification of the workforce. Also, career growth opportunities and social benefits for employees in the chemical industry are only at the middle level, according to the public opinion in the East Bohemia region. The attractiveness of employment in the chemical industry is perceived worse by secondary school students than by the general public.
Přitažlivost studia chemie a zaměstnání v chemickém průmyslu z pohledu české veřejnosti
Keywords: Industry reputation; attractiveness of the study of chemistry; attractiveness of employment in the chemical industry; czech public.; Pověst odvětví; přitažlivost studia chemie; přitažlivost zaměstnání v chemickém průmyslu; česká veřejnost.